EFISIENSI KINERJA SMU ADVENT TOMPASO II DAN SMU ADVENT KLABAT DI SULAWESI UTARA: STUDI PERBANDINGAN - Walean, Ronny Hansje (JBE (Journal of Business and Economics); Volume 6 No.2, 2007 JBE UNKLAB, 2007)
This study focus on the performance efficiency of SMU Advent Tompaso H and SMU Advent Klabat. The main objective is to compare efficiency and productivity so that organizations' management should have a basis in improving the performance of these SMU. The two SMU were analyzed over the period 2001 – 2005 or 10 years in aggregate analysis, using the Data Envelopment Analysis (DEA) - Malmquist. This study identified the sources of technical efficiency and total factor productivity performance (TFP) using combined cross-sectional and panel analysis. Four inputs used were total operating expenses, salaries and wages, number of academic staffs, and number of non-academic staffs. The four outputs are number of students enrolled, number of graduates, total revenues, and total assets. DEA finding show that SMU Advent Klabat obtained the highest TFP score of 1.296 compared to 0.703 for SMU Advent Tompaso II. Overall both SMU have posted negative TFP score of 0.955 (-4.5 % declining TFP per year). The positive Source of TFP for SMU Advent Klabat was both technological change (1.296) and technical efficiency (1.000). Whereas, negative scores of TFP in SMU Advent Tompaso II was due to technological change score of 0.703.